Analisis Determinan Kualitas Lingkungan Di Indonesia - Rahmawati, Devi; Azhar, Zul (Universitas Negeri Padang, 2024)
Abstract This research aims to identify and analyze the impact of factors determining environmental quality in Indonesia. This research is descriptive and quantitative, and the panel data used in the analysis includes cross-section and time series data from 2011 to 2022 for 33 provinces in Indonesia, with data from the Central Statistics Agency and the Ministry of Environment and Forestry. This research uses panel data regression analysis. This research uses a fixed effect model approach. The research results found that: (1) Economic growth in the industrial sector has a significant negative impact on the environmental quality index. (2) The human development index has a significant positive effect on the environmental quality index. (3) Income inequality has an insignificant negative effect on the environmental quality index. (4) Population density has a negative and insignificant effect on the environmental quality index. (5) economic growth in the industrial sector, human development index, income inequality and population density have a significant effect on the quality of life index.